2001
DOI: 10.4049/jimmunol.166.1.262
|View full text |Cite
|
Sign up to set email alerts
|

Control of T Cell Development In Vivo by Subdomains Within the IL-7 Receptor α-Chain Cytoplasmic Tail

Abstract: IL-7/IL-7R signaling functions in both growth and differentiation during T cell development. In this study, we examined the extent these activities were controlled by signaling associated with distinct IL-7Rα cytoplasmic domains by transgenic expression of wild-type or cytoplasmic deletion mutants of IL-7Rα in the thymi of IL-7Rα−/− mice. We show an essential requirement for the tyrosine-containing carboxyl-terminal T domain in restoring thymic cellularity, pro-/pre-T cell progression, and survival. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…Therefore, ␥␦ T cell precursors receive proliferation and survival signals from the IL-7R mainly irrespective of Bcl-2. This can be mediated by a carboxyl-terminal region of the IL-7R␣ through the activation of PI3 kinase and Pim-1 (25,49,50). It is also conceivable that the IL-7R supports the survival of ␥␦ T cells by keeping the transcription of the TCR␥ genes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ␥␦ T cell precursors receive proliferation and survival signals from the IL-7R mainly irrespective of Bcl-2. This can be mediated by a carboxyl-terminal region of the IL-7R␣ through the activation of PI3 kinase and Pim-1 (25,49,50). It is also conceivable that the IL-7R supports the survival of ␥␦ T cells by keeping the transcription of the TCR␥ genes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-7-mediated signals promote the differentiation and maintain the viability of CD4-CD8 ϩ thymocytes (39). The paucity of IL-7-expressing TECs in the cortex corresponds to the lack of IL-7R expression on DP cortical thymocytes (54). In the absence of IL-7 signaling, nonselected DP thymocytes down-regulate bcl-2 expression and undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Tyr 449 plays a crucial role in proliferation and survival of lymphocyte precursors by triggering STAT5 and PI3K activation (6,7). However, there are conflicting reports as to whether the Tyr 449 is required for TCR␥ recombination and ␥␦ T cell development (14,24). Recently, it was reported that IL-7R␣-Phe 449 knock-in mice exhibit reduced but detectable levels of ␥␦ T cells (25).…”
mentioning
confidence: 99%